PERSEPSI SISWA TERHADAP PROSES PEMBELAJARAN ILMU PENGETAHUAN SOSIAL (STUDI KASUS SD NEGERI 020254 KOTA BINJAI) - Nurlia Ginting; Miya Amanda Sembiring (Universitas Quality, 2023)
The purpose of this study was to describe students' perceptions of the social studies learning process at SD Negeri 020254 Binjai City, North Sumatra Province in 2023. The method used in this study was a descriptive quantitative method, while collecting data by observation, interviews and documentation. The results showed that the perceptions of class VII students at SD Negeri 020254 Binjai City, North Sumatra Province towards the social studies learning process were divided into three stages, namely the initial stage, the core learning stage and the closing stage of learning. The initial stage of student learning activities obtained results of 86% which gave a positive response. The core stage of learning obtained 97% results and the closing stage obtained results of 100% positive response so it was concluded that the social studies learning process gave a good response at each stage by students.